Predation impact of the nototheniid fish Trematomus bernacchii on the size structure of the scallop Adamussium colbecki in Terra Nova Bay (Ross Sea, Antarctica). - DELL'ACQUA, OMBRETTA; CHIANTORE, MARIACHIARA; Brey, T.; Vacchi, M. (Polar Biology, 2017)
Biotic interactions are particularly relevant in stable environments, such as the High Antarctic areas. Among them, predation has a key role in structuring com- munity and population variables, including size-frequency distribution. This study aims to quantify the impact of pre- dation by the notothenioid sh Trematomus bernacchii on the Antarctic scallop Adamussium colbecki-size distribu- tion. We developed a model of this impact that estimates the size distribution of the preyed scallop population, tak- ing into account for the predator-size distribution, sex structure, and daily consumption. Comparing this size dis- tribution of the preyed A. colbecki with the living popula- tions at Terra Nova Bay (Ross Sea, Antarctica), we were able to detect a relevant impact of sh predation. Fish-size frequency resulted to be the major factor shaping prey- size structure, with signi cant di erences between preda- tion by males and females. Our ndings, given the key role of the two species in the littoral ecosystem of Terra Nova Bay (Antarctic Special Protected Area 161), fall into the framework of ecosystem management of High Antarctic coastal areas, particularly in the actual context of climate change, and increasing anthropogenic impact.